Дистанционное управление сетевым адаптером - Кувалдин, И. А. (ХНУРЕ, 2012)
The given work is developed to the modem Smart Home systems. The device described in this article is intended for remote control electrical equipment at home or at factories. The remote control can switch load up to kW consumption at a distance 150 m.
Keywords: сетевой адаптер; дистанционное управление